2021
DOI: 10.1002/ps.6607
|View full text |Cite
|
Sign up to set email alerts
|

20E and MAPK signal pathway involved in the effect of reproduction caused by cyantraniliprole in Bactrocera dorsalis Hendel (Diptera: Tephritidae)

Abstract: BACKGROUND It is a common phenomenon that insecticides affect insect reproduction and insect hormones. After cyantraniliprole treatment, the egg production and remating behavior of female Bactrocera dorsalis were affected, a phenomenon of ‘hormesis’ appeared, but the change at the molecular level was unknown. Therefore, we investigated the fertility, insect hormone titers and transcription levels and used RNAi to prove the function of genes, to explore the molecular mechanism of cyantraniliprole causing reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Interestingly, the MAPK signaling pathway was the most significantly enriched pathway. Recent research has shown that cyantraniliprole could regulate the reproduction of Bactrocera dorsalis by affecting 20-hydroxyecdysone through the MAPK signaling pathway (Li et al, 2021b). These results indicated that miRNAs could affect the physiological and developmental pathways of S. frugiperda by the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, the MAPK signaling pathway was the most significantly enriched pathway. Recent research has shown that cyantraniliprole could regulate the reproduction of Bactrocera dorsalis by affecting 20-hydroxyecdysone through the MAPK signaling pathway (Li et al, 2021b). These results indicated that miRNAs could affect the physiological and developmental pathways of S. frugiperda by the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 87%
“…The results showed that the most significantly enriched pathway was MAPK signaling pathway, and insecticide could affect the reproduction of insect via MAPK signal pathway (J. Li et al, 2021). These results would expand the knowledge of miRNAs involved in the regulation of various signal pathways in S. frugiperda.…”
Section: Discussionmentioning
confidence: 78%
“…To reveal the regulatory roles of these differentially expressed miRNAs, GO term and KEGG pathway were performed to predict the functions of the target genes of these differentially expressed miRNAs. The results showed that the most significantly enriched pathway was MAPK signaling pathway, and insecticide could affect the reproduction of insect via MAPK signal pathway (J. Li et al, 2021). These results would expand the knowledge of miRNAs involved in the regulation of various signal pathways in S. frugiperda .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the fecundity assay for the B. dorsalis was conducted using a feeding method with some modifications [ 30 ]. Specifically, ten-day-old female and male flies (10 each) were placed in a plastic cup (250 mL) and fed with artificial food containing osthole at different concentrations (0.0625–2 mg/mL).…”
Section: Methodsmentioning
confidence: 99%